Exploratory Descriptive Study on the Management og Hospital Facilities and Infrastructure - Saleh, Muhammad; Kusumawati, Prima Dewi; Nurwijayanti; Wulandari, Ning Arti; Abiddin, Andi Hayyun (STIKes Patria Husada Blitar, 2025)
Management of facilities and infrastructure has a very important role in the effectiveness of health services, especially in Medical Rehabilitation Installations. Hospitals face challenges related to increasing patient volumes, leading to patient overcrowding and extended waiting times. The aim of this research was to analyze the management of hospital service facilities and infrastructure. The design of this research was exploratory descriptive with a qualitative approach. The subjects of this research were 11 subjects from units related to hospital services at the West Sidoarjo General Hospital. The data collection process was carried out using interviews, observation and documentation. This study showed that improving coordination between management and medical staff as well as improving medical equipment maintenance systems will make a significant contribution to hospitals' ability to meet healthcare needs efficiently. Hospitals need to carry out routine training on the use of medical equipment, form equipment maintenance teams and carry out regular audits.